1956
DOI: 10.1246/bcsj.29.373
|View full text |Cite
|
Sign up to set email alerts
|

On the Base Strength of Some Nitrogen Heterocycles in the Excited State

Abstract: 1. The fluorescence and absorption spectra of aqueous solutions of quinoline, acridine and 2,8-diaminoacridine were observed at various pH values, and it became clear that the stabilization energy by proton addition is larger in the excited state than in the ground state. 2. The effects of hydrogen bonding and proton addition upon the spectra were confirmed to be the same in tendency. 3. On the basis of the fluorescence intensities in various organic solvents, some discussions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…Quinoline is the spectral probe that is stable in supercritical water ͑460°C͒ for about 1 h, 36 and the -* absorbance bands are known to be sensitive to hydrogen bond interactions. [37][38][39] …”
Section: Estimation Of the Degree Of Hydrogen Bonding Between Quinolimentioning
confidence: 99%
“…Quinoline is the spectral probe that is stable in supercritical water ͑460°C͒ for about 1 h, 36 and the -* absorbance bands are known to be sensitive to hydrogen bond interactions. [37][38][39] …”
Section: Estimation Of the Degree Of Hydrogen Bonding Between Quinolimentioning
confidence: 99%
“…5-8). Fhe salts (6,7,8,9, Table 2) have a higher molar absorptivity of the shorter-wavelength transition (340-380 nm).…”
Section: A) Absorptionmentioning
confidence: 99%
“…10-Alkylquindolines may be regarded as conju gated systems composed of two main structural frag ments: indole and quinoline: in both fragments the lowest-lying singlet t]ii* level is below 310 nm [7,8]. According to [9] the energy of the rj n* state is practi cally independent of the length of the conjugated sys tem: consequently the lowest-lying singlet state of the investigated compounds, which is around 450 nm, is of nn* character and is about 10000cm-1 below the > 1 n* level.…”
Section: B) Luminescencementioning
confidence: 99%
“…However, existing measurements of proflavine spectra are done in aqueous and other solutions [16,[19][20][21][22]. It has been found that the optical spectrum of proflavine is very sensitive to the type of a solvent and pH factor [19,21]. There is a possibility that spectra of proflavine and its ions in vacuum and under astrophysical conditions are substantially different from ones in solutions.…”
Section: Introductionmentioning
confidence: 99%